2018
DOI: 10.1063/1.5033561
|View full text |Cite
|
Sign up to set email alerts
|

Carrier scattering mechanisms limiting mobility in hydrogen-doped indium oxide

Abstract: Hydrogen-doped indium oxide (IO:H) has recently garnered attention as a high-performance transparent conducting oxide (TCO) and has been incorporated into a wide array of photovoltaic devices due to its high electron mobility (>100 cm2/V s) and transparency (>90% in the visible range). Here, we demonstrate IO:H thin-films deposited by sputtering with mobilities in the wide range of 10–100 cm2/V s and carrier densities of 4 × 1018 cm–3–4.5 × 1020 cm–3 with a large range of hydrogen incorporation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Meanwhile, the SH-SnO 2 film showed two-fold higher hydrogen intensity than that of the SO-SnO 2 film due to hydrogen incorporation from H-containing species in H 2 O plasma. Notably, hydrogen impurity concentrations in various oxides influence the crystalline structure and electrical properties, like carrier mobility and concentrations [32][33][34]. For example, Husein et al reported that hydrogen-doped indium oxide films showed decreased electron mobility as the hydrogen content was increased to 5.7% [33].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the SH-SnO 2 film showed two-fold higher hydrogen intensity than that of the SO-SnO 2 film due to hydrogen incorporation from H-containing species in H 2 O plasma. Notably, hydrogen impurity concentrations in various oxides influence the crystalline structure and electrical properties, like carrier mobility and concentrations [32][33][34]. For example, Husein et al reported that hydrogen-doped indium oxide films showed decreased electron mobility as the hydrogen content was increased to 5.7% [33].…”
Section: Resultsmentioning
confidence: 99%
“…Polar optical phonon scattering has been generally proposed as the main contributor to phonon scattering in In2O3. [18,19] Using the approximation for polar optical phonon scattering,   T -p , we determined 0.24 < p ≤ 0.45 for the annealed IZRO sample (Figure 2d). This is lower than the p = 2.2 reported for unintentionally doped epitaxially grown In2O3 films.…”
Section: Figure 2cmentioning
confidence: 99%
“…This causes the reduced oxygen content in the surface region, resulting in the formation of oxygen vacancies. 54 While the temperature within the film is high enough, oxygen atoms remain mobile, and they continue to be drawn towards this region resulting in the final increased oxygen gradient within the film. In the oxidising environment, however, the oxygen atoms that escape at the surface are quickly replaced with oxygen atoms from within the pressurised chamber.…”
Section: Reflecting the Oxygen Gradient In The Ellipsometric Modelmentioning
confidence: 99%
“…Finally, it is important to note that annealing in hydrogen has a potential to promote hydrogen doping within the lattice. 54,55 This has been proposed to be a shallow donor that is more energetically favourable than oxygen vacancies. 56 The effect of H-doping during ReLA in 5% H2 in N2 may further enhance the carrier concentration modulation, but analysis of this mechanism is beyond the scope of this work.…”
Section: Reflecting the Oxygen Gradient In The Ellipsometric Modelmentioning
confidence: 99%